A New Species of theSimulium (Simulium) multistriatumSpecies-Group (Diptera: Simuliidae) From Thailand and Its Phylogenetic Relationships With Related Species - Takaoka, Hiroyuki; Srisuka, Wichai; Low, Van Lun; Saeung, Atiporn (Oxford University Press, 2018)
Simulium undecimum sp. Nov. is described from Thailand. This new species is assigned to the Simulium multistriatum species-group, one of the 20 species-groups of the subgenus Simulium in the Oriental Region. It is characterized by the female cibarium with minute processes, male ventral plate with a narrow body having two vertical rows of distinct teeth on the posterior surface and without setae on the anterior and lateral surfaces, pupal gill with eight short filaments decreasing in length from dorsal to ventral, and divergent at an angle of around 90 degrees when viewed laterally, spine-combs only on abdominal segments 7 and 8, and cocoon wall-pocket shaped with anterolateral windows. Taxonomic notes to separate this new species from related species in Thailand and other countries are given. This new species is the 11th nominal member of this species-group recorded in Thailand. An analysis of the COI gene sequences shows that it is most closely related with S. malayense Takaoka & Davies (cytoform A) from Thailand but they are distantly separated by 3.01-8.87%. © 2018 The Author(s).